The Effect of Exposure to Hoaxes About COVID-19 Vaccination on Social Media and Perception in The Health Belief Model on COVID19 Vaccination Behavior: A Cross-Sectional Study of The General Public in Jombang Regency - Sanada, Aldo Sanasta (Universitas Negeri Semarang, 2025)
Background: The spread of hoaxes about COVID-19 vaccination on social media has the potential to influence public perception and vaccination decisions. Perceptions within the Health Belief Model (HBM) also play a crucial role in shaping health behaviors. This study aims to analyze the influence of exposure to COVID-19 vaccination hoaxes and HBM perceptions on vaccination behavior among the general public in Jombang Regency. Method: Quantitative research with cross-sectional designThe study was conducted in October 2022 in Jombang Regency. Respondents were selected using cluster random sampling and consisted of 400 individuals aged 18 years and older who met the inclusion criteria. The independent variables included exposure to COVID-19 vaccination hoaxes on social media and perceptions of the HBM (susceptibility, severity, benefits, and barriers), while the dependent variable was COVID-19 vaccination behavior. The research instrument was a structured questionnaire. Data analysis used the t-test, F test, and multiple linear regression. Results: A total of 400 respondents were analyzed. Exposure to hoaxes negatively impacts vaccination behavior (β=–0.173, p < 0.05; 95% CI–0.20 sd–0.14), while perception in HBM has a positive influence (β= 0.095, p < 0.05; 95% CI 0.07 to 0.12). Simultaneous analysis showed that both variables had a significant effect on vaccination behavior (F = 80.509, p < 0.05) with a contribution of 28.9% (R²= 0.289). Conclusion: Exposure to COVID-19 vaccination hoaxes on social media and perceptions in the Health Belief Model have a significant influence on vaccination behavior. Social media-based educational efforts that emphasize the benefits of vaccination and clarify misinformation need to be strengthened to increase vaccination coverage.